Porous Polymeric Microspheres With Controllable Pore Diameters for Tissue Engineered Lung Tumor Model Development - Dhamecha, Dinesh; Le, Duong; Movsas, Rachel; Gonsalves, Andrea; Menon, Jyothi U. (Frontiers in Bioengineering and Biotechnology, 2020)
Complex cell cultures are more representative of in vivo conditions than conventionally used monolayer cultures, and are hence being investigated for predictive screening of therapeutic agents. Poly lactide co-glycolide (PLGA) polymer is frequently used in the development of porous substrates for complex cell culture. Substrates or scaffolds with highly interconnected, micrometric pores have been shown to positively impact tissue model formation by enhancing cell attachment and infiltration. We report a novel alginate microsphere (AMS)-based controlled pore formation method for the development of porous, biodegradable PLGA microspheres (PPMS), for tissue engineered lung tumor model development. The AMS porogen, non-porous PLGA microspheres (PLGAMS) and PPMS had spherical morphology (mean diameters: 10.3 ± 4 µm, 79 ± 21.8 µm and 103 ± 30 µm respectively). The PPMS had relatively uniform pores and a porosity of 45.5%. The optimized cell seeding density on PPMS was 25 x 103 cells/ mg of particles/ well. Collagen coating on PPMS significantly enhanced the attachment and proliferation of co-cultures of A549 lung adenocarcinoma and MRC-5 lung fibroblast cells. Preliminary proof-of-concept drug screening studies using mono- and combination anti-cancer therapies demonstrated that the tissue-engineered lung tumor model had a significantly higher resistance to the tested drugs than the monolayer co-cultures.